Continuous biogas production from sugarcane as sole substrate - S. Paulsen; K. Hoffstadt; S. Krafft; A. Leite; J. Zang; W. Fonseca-Zang; I. Kuperjans (Energy Reports, 2020)
A German-Brazilian research project investigates sugarcane as an energy plant in anaerobic digestion for biogas production. The aim of the project is a continuous, efficient, and stable biogas process with sugarcane as the substrate. Tests are carried out in a fermenter with a volume of 10~l. In order to optimize the space-time load to achieve a stable process, a continuous process in laboratory scale has been devised. The daily feed in quantity and the harvest time of the substrate sugarcane has been varied. Analyses of the digester content were conducted twice per week to monitor the process: The ratio of inorganic carbon content to volatile organic acid content (VFA/TAC), the concentration of short-chain fatty acids, the organic dry matter, the pH value, and the total nitrogen, phosphate, and ammonium concentrations were monitored. In addition, the gas quality (the percentages of CO2, CH4, and H2) and the quantity of the produced gas were analyzed. The investigations have exhibited feasible and economical production of biogas in a continuous process with energy cane as substrate. With a daily feeding rate of 1.68~~gVS /l*d the average specific gas formation rate was 0.5~m3/kgVS. The long-term study demonstrates a surprisingly fast metabolism of short-chain fatty acids. This indicates a stable and less susceptible process compared to other substrates.
Keywords: 330; Anaerobic digestion; Biogas production; Continuous tests; Space-time load; Sugarcane